Toward a public health leadership national training agenda: a review of conceptual frameworks and core competencies - Burke, Emily M.; Fox, Jordan A.; Tager, Kaitlin; McDowell, Sara; Phelps, Fawn; Koh, Howard (Frontiers in Public Health, 2025)
Strong and effective leadership is essential for the success of public health systems. It serves as the driving force that inspires, guides, and empowers individuals to improve the health of their communities and strengthen their organizations. Leadership is not merely supplementary but a core element in tackling the increasingly complex challenges facing public health today. The COVID-19 pandemic exposed significant weaknesses in our systems for emergency preparedness and response, highlighting just how critical capable leadership is within governmental public health. These challenges are magnified by persistent workforce issues, including knowledge gaps, limited development opportunities, and concerns around long-term sustainability. Further complicating the landscape are rising levels of political polarization and incidents of harassment directed at public health professionals. In response to these pressures and a growing wave of workforce attrition, there is now a heightened national focus on developing the next generation of public health leaders. This development must be intentional and structured, relying on well-designed, competency-based approaches rather than informal or inconsistent methods. Public health leaders must be equipped with the skills to navigate the evolving demands of modern health systems. In 2022, the Association of Schools and Programs of Public Health (ASPPH) convened an expert panel to develop a national leadership training agenda tailored to the governmental public health workforce. The panel consisted of 15 academic and practice leaders in the United States. Between 2022 and 2024, the panel met regularly to define the essential attributes of public health leadership and determine effective strategies for cultivating them through education and capacity-building efforts. The result of this collaborative effort is the ASPPH Public Health Leadership Competency Mapping and Training Agenda: a foundational framework designed to strengthen capabilities across current and future governmental public health professionals. This article presents that framework, marking an important step toward building a more resilient, competent, and adaptive public health workforce.